Implementation Of Accreditation Policy In Hospital Management Information Systems To Improving Employee Performance; Literature Review - Dista Silvie Ayu Marinda; Ratna Wardani; Laili Wulandari (Universitas STRADA Indonesia, 2023)
Efforts made by the Ministry of Health to improve the quality of hospital services are through accreditation activities for both government and private hospitals. The increase in the number of hospitals is very rapid every year, this condition causes competition to occur in providing the best quality service. Researchers assess the need for improving the quality of employee performance to improve service quality.This research method uses a literature review where 4 articles are included in the superior paper category obtained from Google Scholar so that they are good for further analysis. Critical analysis of 4 articles was conducted based on design, population and sample, sampling, treatment, parameters, findings and conclusions.This literature review shows that hospital accreditation has an effect on employee performance, so itis necessary to carry out accreditation as an effort to improve quality.